Monitoring landscape change and urban growth of Bartin, Turkey, and its environmental effects - Gökyer, Ercan; Gökyer, Ercan (Parlar Scientific Publications parlar@masell.com, 2014)
This study aimed to analyse landscape change (LC)/urban growth and its negative effects during a 27-years period of Bartin, Turkey. Landscapes have been impacted over time as a result of human interventions and natural circumstances in the northern part of Turkey. There is a restricted research on LC/urban growth and its negative effects in the city of Bartin and its environments. LC information was derived from remote sensing images acquired in 1986, 2000, and 2013, respectively. The results showed that the urban area of Bartin has expanded approximately four times between 1986 and 2013. In this study, environmental problems that resulted from LC and urban growth, such as floods, air pollution and water pollution, were highlighted and discussed in the study area. © 2015 Elsevier B.V., All rights reserved.
Keywords: Bartin; Landscape Change; Satellite Images; Urban Growth; Urbanization